2018
DOI: 10.3390/polym10070691
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations on the Thermal Decomposition of Meta-Aramid Fibers

Abstract: The thermal decomposition mechanism of a meta-aramid fiber was simulated at the atomic level using the ReaxFF reactive force field. The simulation results indicated that the main initial decomposition positions of the meta-aramid fiber elements were C aromatic ring –N and C=O, which could be used as targets for the modification of meta-aramid fibers. The meta-aramid fiber elements first decomposed into C6–C13 and then into smaller segments and micromolecular gases. The temperature was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…In the 2nd stage, with temperature increase of up to 300 °C, there was suddenly 50% mass degradation. This is confirmed by the previous research in which modacrylic fibers showed similar decomposition behavior [ 36 ].…”
Section: Resultssupporting
confidence: 90%
“…In the 2nd stage, with temperature increase of up to 300 °C, there was suddenly 50% mass degradation. This is confirmed by the previous research in which modacrylic fibers showed similar decomposition behavior [ 36 ].…”
Section: Resultssupporting
confidence: 90%
“…These nonreactive simulations can describe bond stretching, angle bending, dihedral rotations, and nonbonded interactions but not bond breaking or bond formation. There have been MD studies on the thermal , and mechanical degradation , of polymers. However, studies on hydrolytic cleavage of different functional groups in order to understand the chemistry of polymer biodegradation in solvents using atomistic MD techniques have been scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of formic acid on the thermal decomposition of PMIA at different temperatures were explained by fitting the first-order decay expression to the molecular dynamic model; , the initial reaction rates ( k ) of PMIA at various temperatures were obtained. where N 0 is the initial number of PMIA molecules, t is the initial PMIA decomposition time, and N t is the number of PMIA at time t .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The effects of formic acid on the thermal decomposition of PMIA at different temperatures were explained by fitting the first-order decay expression to the molecular dynamic model; 41,42 the initial reaction rates (k) of PMIA at various temperatures were obtained.…”
Section: Resultsmentioning
confidence: 99%